Beyond the Speaker’s Voice: A Phase-Based Syntax for Logophoric Pronouns in Benue-Congo Languages - Nwogu, Aaron Ogbonnah (dialektika kontemporer, 2025)
Logophoric pronouns are a distinctive typological feature of many Benue-Congo languages in Nigeria, providing a morphological window into the syntax of reported speech and attitude. While their referential properties are well known, this paper provides a novel syntactic account of their licensing within the framework of Phase Theory. We argue that the logophoric pronoun is not merely a discourse anaphoric element but a formal syntactic object that must be bound by a logophoric operator in the left periphery of an attitude bearing clause. This operator is base generated in the specifier of a Logophoric Phrase, projected above vP and or CP phases depending on the embedding predicate. Through comparative data from languages like Yoruba, Igbo, and Ebira, we demonstrate that the well documented impenetrability of non attitudinal clauses for logophoricity directly correlates with phase boundaries. A logophoric pronoun must be bound within the same phase where its logophoric operator is merged; extraction across a non logophoric phase edge leads to ungrammaticality. Our analysis successfully predicts the complementizer sensitivity of logophoric pronouns, recasting it as a reflex of phase head agreement. This paper moves the analysis of logophoricity beyond its traditional pragmatic domain, integrating it into the core computational system of syntax and offering a unified model for its cross linguistic manifestations within Nigeria's linguistic landscape.